Effect of Zn Substitution on Magnetic Properties of CuFe2O4: a High-Temperature Series Expansions Study. (January 2018) - Salmi, S.; Masrour, R.; El Grini, A.; Bouslykhane, K.; Hourmatallah, A.; Benzakour, N.; Hamedoun, M.
Abstract : The magnetic properties of spinel ferrites Cu 1− x Zn x Fe 2 O 4 are studied using high-temperature series expansions combined with the Padé approximates. The exchange interactions, inter and intra-sublattices J AA, J BB and J AB are obtained using a probability distribution law. The critical exponent γ associated with the magnetic susceptibility is obtained.